L'élevage du bar et de la daurade en France : viabilité économique des systèmes de production - Pomélie C. de la (Aspects économiques de la production aquacole, 1995)
Three different rearing strategies for sea-bass and sea-bream have rapidly been developed during the last ten years in France: small scale farming in cages in very sheltered areas and industrial farming either off-shore in cages or in-shore in ponds. Production costs of sea-bass in small scale conditions are high, but not above the local market price. Production costs in industrial conditions are much lower and closer to international prices of the European market. Nevertheless, the development of French aquaculture is restricted by the lack of available sites, is faced to monetary disorders of southern European countries and has to compete with the productions of other Mediterranean countries. Therefore, this activity has to be in constant evolution in order to fit the demand of top quality and easy to cook products from European consumers. IFREMER research center in Palavas is aiming at promoting an environment friendly development of French marine aquaculture thanks to two research programmes, the one on closed systems and the other on genetics.
Seminar of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1995/05/17-19, Montpellier (France)